Utilizing nutrient type compounds as anti-bacterial compounds: arginine and cysteine inhibit Salmonella survival in egg white - Ben-Porat, Nir; Ohayon, Amital; Rosenberg, Tali; Musa, Abdulafiz; Petersen, Erik; Mills, Erez (Frontiers in Bioengineering and Biotechnology, 2024)
Because of growing levels of antibiotic resistance, new methods to combat bacteria are needed.We hypothesized that because bacteria evolved to survive in specific environments, the addition of compounds, including nutrient type compounds, to an environment, might result in a modification of that environment that will disrupt bacterial growth or in maladaptive bacterial behavior, i.e., gene expression. As a proof of concept, we focused on the egg white environment and the pathogen Salmonella. Despite egg white's antibacterial nature, Salmonella is able to survive and grow in egg white, and this ability of Salmonella leads to infection of chicks and humans. Here, the 20 L-amino-acids were screened for their ability to affect the growth of Salmonella in egg white. L-arginine and L-cysteine were found to reduce growth in egg white in physiologically relevant concentrations. To determine the mechanism behind L-arginine inhibition TnSeq was utilized. TnSeq identified many Salmonella genes required for survival in egg white including genes required for iron import, biotin synthesis, stress responses, cell integrity, and DNA repair. However, a comparison of Salmonella in egg white with and without L-arginine identified only a few differences in the frequency of transposon insertions, including the possible contribution of perturbations in the cell envelope to the inhibition mechanism.Finally, both D-arginine and D-cysteine were found to inhibit Salmonella in egg white. This implied that the effect of arginine and cysteine in egg white is chemical rather than biological, likely on the egg white environment or on the bacterial outer membrane. To conclude, these results show that this approach of addition of compounds, including nutrient type compounds, to an environment can be used to limit bacterial growth. Importantly, these compounds have no inherent anti-bacterial properties, are used as nutrients by animals and bacteria, and only become anti-bacterial in a specific environmental context. Future research screening for the effects of compounds in relevant environments might uncover new ways to reduce pathogen levels in the poultry industry and beyond.